Depression und Diabetes mellitus Typ 2 - Deuschle, Michael; Schweiger, Ulrich (Der Nervenarzt, 2012)
Depression and diabetes mellitus type 2 are frequently comorbid conditions. Both disorders may increase the incidence of the other disorder and impair the prognosis. Thus, it is important for psychiatrists to consider depressed patients as high-risk diabetes subjects to screen for metabolic risks and to consider metabolic risks of antidepressant treatment.